The mediating role of adolescent autonomous value-driven decision-making in the relationship between maternal-adolescent relationship quality and adolescent internalizing experiences: a longitudinal study - Jones, Benjamin (Kansas State University, 2023)
Research has demonstrated the positive associations of both parent-adolescent relationship quality and adolescent autonomy development on adolescent mental health outcomes, yet less is known about the role that autonomy development may play in helping to explain the impact of high quality relationships on mental health outcomes for adolescents. Using data from Waves 4, 5, and 6 of the The Flourishing Families study, this study explored the mediating role of adolescent autonomous value-driven decision-making at Wave 5 in the relationship between maternal-adolescent relationship quality at Wave 4 and adolescent internalizing experiences at Wave 6. These factors were examined based on adolescent report through structural equation modeling techniques that modeled maternal-adolescent relationship quality, adolescent autonomous value-driven decision-making, adolescent depression, and adolescent anxiety as latent variables. In addition to exploring the direct relationships between constructs at subsequent waves, indirect effects between maternal-adolescent relationship quality and adolescent internalizing experiences were tested via the mediating pathway of adolescent autonomous value-driven decision making. Tests of moderated mediation were also conducted via the use of multiple group structural equation modeling techniques to test for any sex-based differences in the model. Results indicated that maternal-adolescent relationship quality at Wave 4 was significantly and positively associated with adolescent autonomous value-driven decision-making at Wave 5, and adolescent autonomous value-driven decision-making was significantly and negatively associated with adolescent depression at Wave 6. Significant indirect effects were detected from maternal-adolescent relationship quality to adolescent depression via the mediating pathway of adolescent autonomous value-driven decision-making.
Keywords: Adolescents; Depression; Anxiety; Autonomy; Maternal; Relationship